Penegakan Hukum terhadap Operasional Motor ATV pada Jalan Umum di Kabupaten Gianyar - I Made Raditya Pratama; Luh Putu Suryani; I Ketut Sukadana (Jurnal Hukum Lex Generalis, 2025)
ATV operation in Gianyar Regency frequently takes place on public roads. This study aims to analyze legal violations and the effectiveness of law enforcement. The method used is empirical research through observation and interviews. The results of the study indicate violations of Law No. 22 of 2009 on Road Traffic and Transportation, particularly regarding vehicle technical compliance, registration, and the use of vehicles on public roads, as well as Government Regulation No. 55 of 2012 on Vehicles concerning technical requirements and roadworthiness. Law enforcement is considered fairly effective, with periodic joint raids and the requirement for business operators to use dedicated lanes.